Разработка и внедрение калибраторов с прерывистыми лопастями - Бочковский, А.М. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
Dependence for definition of loading on inserts of the calibrator is received. Calibrators of a new design with the increased number of faltering blades and hydraulic ring apertures between them are developed. Resistance of new calibrators in 3-5 times exceeds resistance of the serial tool.